Pengaruh Uang Saku dan Gaya Hidup Hedonis Remaja terhadap Proses Keputusan Pembelian Makanan Cepat Saji Burger King di Kota Makssar dengan Perilaku Konsumtif sebagai Variabel Intervening - Alfarid, Eko; Akil Rahman, Muhammad; Abdullah, Wahidah (Universitas Islam Negeri Alauddin Makassar, Indonesia, 2023)
This research aims to examine the influence of pocket money and the hedonistic lifestyle of adolescents on the decision process of buying fast food with consumptive behaviour as an intervening variable. In this study the variables used are pocket money and hedonistic lifestyle as independent variables, the purchase decision process as a depedent variable, consumptive behavior as an intervening variable (mediation). This research is quantitative research. The data source in this study is sourced from primary data which the data collection method uses a questionnaire method that is distributed to all teenagers in Makassar city. The number of samples used was 100 respondents. With primary data management by using path analysis using the help of Statistical Package for Social Sciencee (SPSS) Software. The results of this study show that partially it wass found that the support of pocket money variables and hedonistic lifestyle variables had a positive and significant effect on the Burger King fast food purchase decision process in Makassar City. Partially pocket money is negative and has no significance influence on consumptive behaviour and hedonistic lifestyle has a positive and significant effect on consumptive behaviour. Indirectly pocket money, and a hedonistic lifestyle affect the purcase decision process through consumptive behaviour. Keywords: Pocket Money, Hedonic Lifestyle, Purchasing Decision Process, Consumptive Behaviour.